Refugees, immigrants, and education in the global south : lives in motion - Bartlett, Lesley; Ghaffar-Kucher, Ameena (New York : Routledge, 2013)
"The unprecedented human mobility the world is now experiencing poses new and unparalleled challenges regarding the provision of social and educational services throughout the global South. This volume examines the role played by schooling in immigrant incorporation or exclusion, using case studies of Thailand, India, Nepal, Hong Kong/PRC, the Philippines, the United Arab Emirates, Jordan, Kenya, Egypt, South Africa, Senegal, Sudan, Mexico, and the Dominican Republic. Drawing on key concepts in anthropology, the authors offer timely sociocultural analyses of how governments manage increasing diversity and how immigrants strategize to maximize their educational investments. The findings have significant implications for global efforts to expand educational inclusion and equity"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Refugees -- Education -- Southern Hemisphere; Immigrants -- Education -- Southern Hemisphere; Comparative education; Electronic books